Zur Definition der Präposition im Deutschen - Darski, Józef Paweł (Studia Germanica Posnaniensia, 2018)
The article is a critical analysis of the hitherto definitions of preposition in German grammar and the author suggests his own definition based on the analogy with the infinitive. Preposition is, according to the author, a particle devoid of the importance of the part of a sentence and having the value similar to that of an infinitive.